Mutational analysis of TSC1 and TSC2 genes in Tuberous Sclerosis Complex patients from Greece. Issue 1 (December 2017) - Avgeris, Socratis; Fostira, Florentia; Vagena, Andromachi; Ninios, Yiannis; Delimitsou, Angeliki; Vodicka, Radek; Vrtel, Radek; Youroukos, Sotirios; Stravopodis, Dimitrios; Vlassi, Metaxia; Astrinidis, Aristotelis; Yannoukakos, Drakoulis; et al.
Abstract Tuberous sclerosis complex (TSC) is a rare autosomal dominant disorder causing benign tumors in the brain and other vital organs. The genes implicated in disease development areTSC1 andTSC2 . Here, we have performed mutational analysis followed by a genotype-phenotype correlation study based on the clinical characteristics of the affected individuals. Twenty unrelated probands or families from Greece have been analyzed, of whom 13 had definite TSC, whereas another 7 had a possible TSC diagnosis. Using direct sequencing, we have identified pathogenic mutations in 13 patients/families (6 inTSC1 and 7 inTSC2 ), 5 of which were novel. The mutation identification rate for patients with definite TSC was 85%, but only 29% for the ones with a possible TSC diagnosis. Multiplex ligation-dependent probe amplification (MLPA) did not reveal any genomic rearrangements inTSC1 andTSC2 in the samples with no mutations identified. In general, TSC2 disease was more severe than TSC1, with more subependymal giant cell astrocytomas and angiomyolipomas, higher incidence of pharmacoresistant epileptic seizures, and more severe neuropsychiatric disorders. To our knowledge, this is the first comprehensiveTSC1 andTSC2 mutational analysis carried out in TSC patients in Greece.